On the $n$-similarity of the operators which are left inverse to the $n^{th}$ degree of the integration operator in the spaces of analytic functions - Zvozdetskyi, T.I. (Carpathian Mathematical Publications, 2012)
We investigate the conditions of the $n$-similarity of the $n^{\rm th}$ degree of the differentiation operator to an operator which is left inverse to the $n^{\rm th}$ degree of the integration operator in the spaces of analytic functions.